Experimental and Numerical Analysis of Wave Drift Force on KVLCC2 Moving in Oblique Waves - Min Guk Seo; Yoon Jin Ha; Bo Woo Nam; Yeongyu Kim (Journal of Marine Science and Engineering, 2021)
In this study, experimental and numerical methods were applied to estimate surge and sway wave drift forces and yaw drift moment acting on KVLCC2, advancing in oblique wave. An experiment was carried out in the ocean engineering basin of the Korea Research Institute of Ships and Ocean Engineering (KRISO). A series of regular wave tests under various heading conditions were conducted to investigate ship motion responses and wave drift forces. A Rankine panel method based on potential flow was adopted in the numerical analysis, and the direct pressure integration method that integrates second-order pressure on the hull surface was applied to compute wave drift force. Through this study, validation data of wave drift force acting on KVLCC2 was established, and the computation capability of the potential-based numerical method was systematically analyzed.